Alauda arvensis subsp. herberti Hartert - LeCROY, M. A. R. Y. (Zenodo, 2003)
Alauda arvensis herberti Hartert Alauda arvensis herberti Hartert, 1923d: 149 (Bangkok, Siam). Now Alauda gulgula herberti Hartert, 1923. See Peters, 1960a: 70, Robson, 2000: 476, and Dickinson et al., 2001a: 93. LECTOTYPE: AMNH 555589, adult male, collected in Bangkok, 13°44′N, 100°30′E (Times Atlas), Thailand, on 31 March 1915, by W.J.F. Williamson. From the Rothschild Collection. COMMENTS: In the original description, Hartert (1923d: 149) said that the type, an adult male collected by Williamson on 31 March 1915, was in the Rothschild Museum; in his list of Rothschild types, he (Hartert, 1928: 210) did not add any further information. There are two adult males collected on 31 March 1915, which would therefore have to be considered syntypes. The above specimen, AMNH 555589, bears the Rothschild type label and the Rothschild Collection label marked ‘‘Type of Alauda arvensis herberti Hartert’’ in Hartert’s hand. It is undoubtedly the specimen intended as the type and I hereby designate it the lectotype to remove the ambiguity. The paralectotype is AMNH 555591. Hartert (1923d: 149) gave measurements of four males (88–91 mm) and one female (85.5 mm), all from Bangkok. In fact, five males and one female in the type series came to AMNH with the Rothschild Collection. Four of the males and the female were collected by Williamson in February–June 1915 (AMNH 555589–555593), and a juv. male, AMNH 555588, was collected on 6 July 1919 by E.G. Herbert, for whom the taxon was named. Herbert noted that he collected this specimen and saw several other juveniles that had ‘‘nearly finished moulting from the whitetipped feathers, and have no tail feathers. ’’. This specimen is indeed without tail feathers, and the third primary from the outside is growing. Hartert would not have included its measurements, and its wing measures only 80.0 mm. Hartert (1923d: 149) indicated that he included wing measurements of the four males collected by Williamson; however, AMNH 555592 has the outer primaries worn and badly broken. While this ...